Connecting mononuclear dysprosium single-molecule magnets to form dinuclear complexes via in situ ligand oxidation. Issue 4 (16th November 2015) - Yutronkie, Nathan J.; Kühne, Irina A.; Korobkov, Ilia; Brusso, Jaclyn L.; Murugesu, Muralee
Abstract : A Dy2 complex, exhibiting SMM behaviour, and its Y analogue were prepared via in situ oxidation of Py2 TTA, a pincer type ligand, followed by dimerisation. Abstract : A Dy2 complex, exhibiting SMM behaviour, and its Y analogue were prepared via in situ oxidation of Py2 TTA, a pincer type ligand, followed by dimerisation. This unique metal complexation and subsequent dimerization were followed by solution NMR studies.